Simulasi Sistem Parkir Mal Berbasis Lokasi Kunjungan User Menggunakan Mikrokontroler ATMEGA328 dan RFID - Randy, Randy (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2018)
In everyday human activities certainly involved in parking activity, either parked vehicle two wheeled or four, in a parked vehicle can be parked anywhere there is provided and some are not. Sometimes visitor must drive more than once to get a wanted parking spot. The result of this research is a parking system simulation that can provide parking location to a user based on the location of traffic you want, by using the coordinates of the lot parking and outlet to be visited, using the formula Euclidean to calculate and compare the distance.Keywords: Parking system, Mall, destination location